Effects of lactalbumin enzymatic hydrolysate on human squamous cell carcinoma cells-an in vitro study - Agustina Putri Kintan Arini; Worachat Namangkalakul; Phoonsuk Limraksasin; Thanaphum Osathanon (Elsevier, 2024)
Objectives: Alpha-lactalbumin, the protein from human and bovine milk has been found to be promising as an alternative of anticancer agent. This study was aimed to investigate the effects of lactalbumin enzymatic hydrolysate (LAH) on cell proliferation, migration, and mRNA expression of matrix metalloproteinase (MMP) on human squamous cell carcinoma (hSCC) cell lines, in vitro. Methods: Tongue (HSC-4 and 7) and pharyngeal (HN-30 and 31) hSCC cell lines were treated with a two-fold dilution of LAH (0.39-100 mg/ml). Cell viability and cell proliferation were examined by MTT assay. Colony forming unit (CFU) was assessed by crystal violet blue staining. Cell migration was investigated by scratch wound healing assay. Gene expression of metastasis-associated MMPs was assessed by RT-qPCR. Statistical analyses were evaluated at p value = 0.05. Results: LAH at concentration of 50 and 100 mg/ml exhibited cytotoxicity on hSCC cells. The proliferation and CFU ability of hSCC cells were significantly attenuated after LAH treatment. The mRNA expression of MMP2, MMP9, and MMP14 was reduced in HN-30 and HN-31 cells while expression of MMP2 and MMP14 was downregulated in HSC-7 cells. Only MMP1 mRNA level was reduced in HSC-4 cells. However, cell migration of all hSCC cell lines did not alter after LAH treatment. Conclusion: LAH treatment exhibits inhibitory effects on hSCC cell growth, proliferation and MMPs gene expression. Thus, LAH should be the promising alternative agent to develop the prospective anti-cancer drug.